The Influence of Various Strategic Orientation Dimensions on Micro Business Performance in Depok City - Ridwan Mahmudi, Ridwan Mahmudi; Mariati Tamba, Mariati Tamba; Tri Suratmi, Tri Suratmi (LPPM Universitas Respati Indonesia, 2023)
Micro Enterprises are the largest in number (98.68%) and also contribute large employment, namely 89.04%. However, its contribution to GDP is still small, namely only 37.77%. Therefore, in order for the contribution to increase, the performance of micro-enterprises must be improved. The research objective was to analyze the effect of various Strategic Orientation Dimensions on the performance of micro-enterprises in Depok City. This research is a quantitative research, survey method with a causality design. The data used is primary data through filling out questionnaires from 300 micro businesses in the city of Depok. The research design used in this study is a hypothesis test (Testing Hypothesis) using AMOS and SPSS programming. The results showed that all the hypotheses tested gave positive results. Market Orientation, Entrepreneurship Orientation, Technology Orientation and Learning Orientation, partially or simultaneously affect the performance of micro businesses. The conclusion of this study is that strategic orientation has a positive effect on micro businesses. Suggestions from this study are that micro-entrepreneurs run their businesses in accordance with a strategic orientation and the government supports micro-enterprises by conducting coaching based on strategic orientation. Keywords:orientation, strategic, market, entrepreneurship, technology, learning, performance, micro business